Disposable p-coumaric acid sensor containing reduced graphene oxide, nickel nanoparticles and biodegradable molecularly imprinted polymer for fruit peel analysis - Buffon, Edervaldo [UNESP] (2023)
This work reports the development of a disposable molecularly imprinted electrochemical sensor based on the electropolymerization of 3-indoleacetic acid on an electrode containing reduced graphene oxide and nickel nanoparticles for the sensitive and selective detection of p-coumaric acid. The molecularly imprinted sensor was characterized by cyclic voltammetry, electrochemical impedance spectroscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy. The obtained results showed that reduced graphene oxide and nickel nanoparticles increased the sensitivity of the sensor for selective recognition of p-coumaric acid. Under optimal conditions, the developed sensor presented linear concentration ranges from 1.0 × 10−10 to 1.0 × 10−8 mol L−1. The detection and quantification limits calculated for this sensor were 8.1 × 10−11 and 2.7 × 10−10 mol L−1, respectively. The proposed device exhibited excellent selectivity, repeatability and stability over time, as well as good accuracy for the detection of p-coumaric acid. As a proof of concept, the sensor was applied for the determination of this molecule in banana and orange peels. The mean recovery values obtained during the analyses ranged from 96% to 102%, with relative standard deviations of ≤ 4.8%.